Knowledge Updating by Doctors of Academic and Research Institutions in Chennai: A Study - Godwin Rajesh, W.; Ambuja, R. (Journal of Information and Knowledge, 2020)
Innovations in Information, Communication and Technology, have an impact in every domain. Updating knowledge becomes mandatory in the competitive environment. It is useful to study knowledge updating among doctors in academic and research institutions. Knowledge updating by doctors were analyzed based on impact of digital information, Purpose of updating knowledge, mode, method and time spent. The study has been carried out to identify the inquisitiveness among doctors of academic and research institutions in updating their knowledge. Further, the study also enables to identify the impact of digital information. A structured questionnaire was distributed among 605 faculty members of five private medical colleges in Chennai, roughly about 40% of the total faculty strength in each institution. The data were collected during August to December 2019. Out of 605 questionnaires distributed 497 were received. The response rate works out 82.15%. Nearly 82.3% of the respondents have indicated that the digital information has high impact.